Analisa Meningkatnya Rugi-Rugi Daya Akibat Jatuh Tegangan Pada Proses Transmisi 150 KV Maligi-Indoliberty - M Haikal Ismawan; Dian Budhi Santoso (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2021)
Tariffs are one of the driving forces of the economy, so electrical energy providers should be more effective in presenting electrical energy so that the basic electricity tariffs can be cheaper, one way is to reduce power losses in the transmission process. power losses arise because the transmission conductor has resistance values, power losses can increase if the voltage in the transmission system decreases, in the case study taken at PT PLN (Persero) UPT Karawang Gardu Induk (GI) 150 KV maligi the direction of the conductor Indoliberty 150 KV transmission when the average load in one day is 18.85 MW and 10.01 MVAr there is a power loss of 7065.05 W in one day when the voltage is 150 KV, and power losses increase by 411.17 W when there is avoltage drop of 2.8766% from a voltage of 150 KV to 145.82 KV which increases the cost loss of Rp. 9838,396 per day.